Applied Gamification: Reframing Evaluation in Post-Secondary Classrooms. Issue 2 (3rd April 2017) - Kulpa, Anastasia
ABSTRACT: This piece reports on an early attempt at gamification (reframing post-secondary classrooms drawing on the structure of games). The attempt began in the 2011–2012 academic year and is structured to allow students substantial autonomy in determining which assignments, and how many of them, to complete over the course of the semester. Initial results show small increases in overall student achievement and suggest students may take greater risks in their learning in gamified classrooms. Themes in student responses to gamified classrooms are reported, challenges for both faculty and students in employing such an approach (e.g., pacing student work, confronting assumptions about the nature of academic work, and communicating the nature of the system) are discussed, along with strategies that can help address them.